2020
DOI: 10.1002/cam4.3061
|View full text |Cite
|
Sign up to set email alerts
|

The underlying mechanisms of lorlatinib penetration across the bloodbrain barrier and the distribution characteristics of lorlatinib in the brain

Abstract: Objective: To clarify the distribution of lorlatinib in the brain and elucidate the molecular mechanisms of lorlatinib penetration across the blood-brain barrier (BBB). Methods: Cytological experiments were performed to investigate the growth inhibitory effect of lorlatinib on different cells (endothelial cells HUVEC, HMEC-1, and HCMEC/D3) and to investigate the protective effect of lorlatinib on neuronal cells after SH-SY5Y hypoxia/reoxygenation injury. Furthermore, rat brain tissue was sequenced, and the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…P-glycoprotein, an ATP-binding cassette (ABC) transporter, which is a major pump that transports promiscuous xenobiotics out of cells, associates with multidrug resistance (MDR) due to overexpression ( Cannon et al, 2012 ; Mollazadeh et al, 2018 ; Ren and Gray, 2019 ). In a previous study, through RNA sequencing, we confirmed that lorlatinib did not exhibit a significant regulatory effect on the p-glycoprotein via mRNA transcription ( Chen et al, 2020 ). However, sphingolipid, signaling via S1P and acting via S1PR1, appears to induce a fast and reversible regulatory effect resulting in low p-glycoprotein pump activity level and an improvement in the delivery of small-molecule compounds to the brain ( Cannon et al, 2012 ).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…P-glycoprotein, an ATP-binding cassette (ABC) transporter, which is a major pump that transports promiscuous xenobiotics out of cells, associates with multidrug resistance (MDR) due to overexpression ( Cannon et al, 2012 ; Mollazadeh et al, 2018 ; Ren and Gray, 2019 ). In a previous study, through RNA sequencing, we confirmed that lorlatinib did not exhibit a significant regulatory effect on the p-glycoprotein via mRNA transcription ( Chen et al, 2020 ). However, sphingolipid, signaling via S1P and acting via S1PR1, appears to induce a fast and reversible regulatory effect resulting in low p-glycoprotein pump activity level and an improvement in the delivery of small-molecule compounds to the brain ( Cannon et al, 2012 ).…”
Section: Discussionsupporting
confidence: 64%
“…In the preliminary experiment, we sequenced the RNA of the control group and the lorlatinib group mice ( Chen et al, 2020 ). By using DEGseq algorithm, |log2Fold Change| ≥1 and Adjusted p value ≤0.001 as the screening criteria, 126 differentially expressed genes were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations